2008
DOI: 10.1038/oby.2008.353
|View full text |Cite
|
Sign up to set email alerts
|

Is Obesity Associated With Anemia of Chronic Disease? A Population‐based Study

Abstract: Obesity is characterized by chronic, low-grade, systemic inflammation, which, in turn, has been associated with anemia of chronic disease. We hypothesized that obesity may be associated with the features of anemia of chronic disease, including low hemoglobin concentration, low serum iron and transferrin saturation (TS), and elevated serum ferritin. We compared normal-weight to overweight and obese adult participants of the third National Health and Nutrition Examination Survey with respect to hemoglobin concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
127
8
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(162 citation statements)
references
References 29 publications
(36 reference statements)
19
127
8
8
Order By: Relevance
“…The results of our study however showed that BMI had no association with haemoglobin, MCV, and other red cell indices. This result contradicts other previous studies [26,27] but is in correlation with other recent works by Akram et al [28] and the work of Manal et al [29]. Our observation is directly backed by the apparent lack of increase in the red blood cells, haematocrit or haemoglobin in the BMI subgroup analyses.…”
Section: Discussioncontrasting
confidence: 57%
“…The results of our study however showed that BMI had no association with haemoglobin, MCV, and other red cell indices. This result contradicts other previous studies [26,27] but is in correlation with other recent works by Akram et al [28] and the work of Manal et al [29]. Our observation is directly backed by the apparent lack of increase in the red blood cells, haematocrit or haemoglobin in the BMI subgroup analyses.…”
Section: Discussioncontrasting
confidence: 57%
“…Several studies have shown no excess risk of anemia in patients with obesity despite increased inflammation and functional iron deficiency related to the hepcidin increase (15,31,32). We previously described a 40% lower risk of anemia in obese patients in the Nephrotest cohort (15).…”
Section: Discussionmentioning
confidence: 99%
“…This was previously confirmed in this elderly community (12) and it seems as if it has remained unchanged. It has recently been found that obesity is associated with chronic, low-grade systemic inflammation which may be associated with IDA, specifically raised ferritin, low serum Fe and low Hb levels (25) . In the present study, higher hs-CRP levels were observed in the overweight and obese categories of both women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Because obesity is characterised by chronic low-grade inflammation, it may be related to the characteristics of anaemia inflammation such as raised serum ferritin, low serum Fe and low Hb levels (25) . hs-CRP was positively associated with BMI, thus inflammation was associated with overweight and obesity in the present study.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%